Functional characterization of a second pedal peptide/orcokinin‐type neuropeptide signaling system in the starfish Asterias rubens. Issue 5 (18th December 2017) - Lin, Ming; Egertová, Michaela; Zampronio, Cleidiane G.; Jones, Alexandra M.; Elphick, Maurice R.
Abstract: Molluscan pedal peptides (PPs) and arthropod orcokinins (OKs) are prototypes of a family of neuropeptides that have been identified in several phyla. Recently, starfish myorelaxant peptide (SMP) was identified as a PP/OK‐type neuropeptide in the starfish Patiria pectinifera (phylum Echinodermata). Furthermore, analysis of transcriptome sequence data from the starfish Asterias rubens revealed two PP/OK‐type precursors: an SMP‐type precursor ( A. rubens PP‐like neuropeptide precursor 1; ArPPLNP1) and a second precursor (ArPPLNP2). We reported previously a detailed analysis of ArPPLNP1 expression in A. rubens and here we report the first functional characterization ArPPLNP2‐derived neuropeptides. Sequencing of a cDNA encoding ArPPLNP2 revealed that it comprises eleven related neuropeptides (ArPPLN2a‐k), the structures of several of which were confirmed using mass spectrometry. Analysis of the expression of ArPPLNP2 and neuropeptides derived from this precursor using mRNA in situ hybridization and immunohistochemistry revealed a widespread distribution, including expression in radial nerve cords, circumoral nerve ring, digestive system, tube feet and innervation of interossicular muscles. In vitro pharmacology revealed that the ArPPLNP2‐derived neuropeptide ArPPLN2h has no effect on the contractility of tube feet or the body wall‐associated apical muscle, contrasting with the relaxing effect of ArPPLN1b (ArSMP) on these preparations. ArPPLN2h does, however, cause dose‐dependent relaxation of cardiac stomach preparations, with greater potency/efficacy than ArPPLN1b and with similar potency/efficacy to the SALMFamide neuropeptide S2. In conclusion, there are similarities in the expression patterns of ArPPLNP1 and ArPPLNP2 but our data also indicate specialization in the roles of neuropeptides derived from these two PP/OK‐type precursors in starfish. Abstract : ArPPLNP2 is a precursor of pedal peptide/orcokinin (PP/OK)‐type neuropeptides (red) that are expressed in the circumoral nerve ring (shown here) and other parts of the starfish Asterias rubens . PPLN2‐type neuropeptides cause stomach relaxation in A. rubens, which contrasts with myoexcitatory effects of PP/OK‐type neuropeptides in protostomian invertebrates (e.g., mollusks, arthropods).